Crystallizing membrane proteins using lipidic mesophases. - CAFFREY, MARTIN (My University, 2009)
A detailed protocol for crystallizing membrane proteins that makes use of lipidic mesophases is described. This has variously been referred to as the lipid cubic phase or in meso method. The method has been shown to be quite general in that it has been used to solve X-ray crystallographic structures of prokaryotic and eukaryotic proteins, proteins that are monomeric, homo- and hetero-multimeric, chromophore-containing and chromophore-free, and ?-helical and ?-barrel proteins. Its most recent successes are the human engineered ?2-adrenergic and adenosine A2A G protein-coupled receptors. Protocols are provided for preparing and characterizing the lipidic mesophase, for reconstituting the protein into the monoolein-based mesophase, for functional assay of the protein in the mesophase, and for setting up crystallizations in manual mode. Methods for harvesting micro-crystals are also described. The time required to prepare the protein-loaded mesophase and to set up a crystallization plate manually is about one hour.
PUBLISHED
Keywords: thin layer chromatography; polarized light microscopy